Does oral health affect self perceptions, parental ratings and video-based assessments of children’s smiles? - Patel RR, Tootla R, Inglehart MR. (Blackwell Synergy, 2007)
To explore whether there is a relationship between children’s objectively determined oral health status and their oral health-related quality of life, specifically the evaluations of their smiles as assessed by the children, their parents, and through measurements of the children’s videotaped smiles.